The last will be first: water transfers from agriculture to cities in the Pangani River Basin, Tanzania - Komakech, H.C.; Zaag, P. van der; van Koppen, Barbara (2012)
Water transfers to growing cities in sub-Sahara Africa, as elsewhere, seem inevitable. But absolute water entitlements in basins with variable supply may seriously affect many water users in times of water scarcity. This paper is based on research conducted in the Pangani river basin, Tanzania. Using a framework drawing from a theory of water right administration and transfer, the paper describes and analyses the appropriation of water from smallholder irrigators by cities. Here, farmers have over time created flexible allocation rules that are negotiated on a seasonal basis. More recently the basin water authority has been issuing formal water use rights that are based on average water availability. But actual flows are more often than not less than average. The issuing of state-based water use rights has been motivated on grounds of achieving economic efficiency and social equity. The emerging water conflicts between farmers and cities described in this paper have been driven by the fact that domestic use by city residents has, by law, priority over other types of use. The two cities described in this paper take the lion's share of the available water during the low-flow season, and at times over and above the permitted amounts, creating extreme water stress among the farmers. Rural communities try to defend their prior use claims through involving local leaders, prominent politicians and district and regional commissioners. Power inequality between the different actors (city authorities, basin water office, and smallholder farmers) played a critical role in the reallocation and hence the dynamics of water conflict. The paper proposes proportional allocation, whereby permitted abstractions are reduced in proportion to the expected shortfall in river flow, as an alternative by which limited water resources can be fairly allocated. The exact amounts (quantity or duration of use) by which individual user allocations are reduced would be negotiated by the users at the river level.